Irreversible Site‐Specific Hydrazinolysis of Proteins by Use of Sortase1. Issue 8 (27th January 2014) - Li, Yi‐Ming; Li, Yi‐Tong; Pan, Man; Kong, Xiu‐Qi; Huang, Yi‐Chao; Hong, Zhang‐Yong; Liu, Lei
Abstract Sortase‐mediated hydrazinolysis of proteins with hydrazine or its derivatives was developed for the production of recombinant protein hydrazides. This process provides an alternative approach for protein semisynthesis through the use of recombinant protein hydrazides as thioester surrogates. It also provides an alternative method for C‐terminal modification of proteins with functional units as well as for the preparation of C‐to‐C fusion proteins.